2006
DOI: 10.3354/meps306223
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biogenic habitat on the recruitment and distribution of a subtidal xanthid crab

Abstract: Biogenic habitat can structure marine communities by serving as both a complex substrate and food source for adult and recruiting organisms. We investigated the role played by biogenic habitats (Mytilus edulis and Crepidula spp. beds) in influencing the subtidal distribution (kilometers scale) of the mud crab Dyspanopeus sayi in Narragansett Bay, New England (USA). In field surveys, D. sayi were 1 to 2 orders of magnitude more abundant on M. edulis and Crepidula spp. beds than at sites lacking these habitats, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
(37 reference statements)
1
25
0
Order By: Relevance
“…In a similar study [33], it was shown that the geometric complexity of the habitat was ecologically more important than food availability for settling megalopae of Dyspanopues sayi .Similar results were found for Carcinus maenas and Paralithodes camtschaticus [28], [48]. This indicates that the findings in this study, independent of field conditions, confirm the great relevance of predation as an indirect control on the settlement process of decapod megalopae.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In a similar study [33], it was shown that the geometric complexity of the habitat was ecologically more important than food availability for settling megalopae of Dyspanopues sayi .Similar results were found for Carcinus maenas and Paralithodes camtschaticus [28], [48]. This indicates that the findings in this study, independent of field conditions, confirm the great relevance of predation as an indirect control on the settlement process of decapod megalopae.…”
Section: Discussionsupporting
confidence: 84%
“…Although these factors have been recognized as key in the settlement process, there are few studies that assess a trade-off between them and their relative effect on settlement success in brachyurans [5], [33], [34].…”
Section: Introductionmentioning
confidence: 99%
“…Other preferred habitats are oyster reefs, mussel beds, the bodies of red-beard sponge Clathria prolifera (Ellis & Solander, 1786), seagrass meadows, rocks and coarse gravel (McDermott & Flower, 1952;Strieb et al, 1995;Mizzan, 1999). Structural complexity is the primary factor influencing D. sayi preferential recruitment on biogenic habitats; later adults also respond positively to the prey value of the engineering species (Lindsey et al, 2006).…”
Section: Habitat Choice and Usementioning
confidence: 99%
“…Increased ability for anaerobiosis induced by aerial exposure should lead to greater tolerance for submergence in hypoxic water as well. This study was conducted in Narragansett Bay, Rhode Island, USA, where mussels create essential habitat that structures the distribution of associated infauna (Lindsey et al 2006). Severe eutrophication in Narragansett Bay generates periods of water-column hypoxia which can lead to local extinction of the mussels and loss of their ecological functions .…”
Section: Introductionmentioning
confidence: 99%